Respuesta :
going off of what jdoe0001 said... the answer is f^-1(3)=23 in the form you need for the answer :)
The value of the expression f^−1(3) is 23
How to determine the value of the expression f^-1(3)?
The equation of the function is given as:
[tex]f(x) = \log_3(x + 4)[/tex]
Set the function to 3
[tex]3 = \log_3(x + 4)[/tex]
Represent as an exponential function
3^3 = x + 4
Evaluate the exponent
27 = x + 4
Subtract 4 from both sides
x = 23
Hence, the value of f^−1(3) is 23
Read more about inverse functions at:
https://brainly.com/question/14391067
#SPJ2